Nutritional and technological properties of a quinoa (Chenopodium quinoa Willd.) : Spray-dried powdered extract - Romano, Nelson Gastón (2019)
The relevance of an appropriate nutrition requires innovation in the design of food ingredients. The goal of this work was to obtain a powdered extract of quinoa by using spray-drying. To this aim, quinoa flour was suspended in water to obtain a soluble fraction mainly composed of proteins, starch, fiber, lipids, antioxidants and minerals. The spray-drying conditions of this quinoa soluble fraction were set-up in terms of inlet temperatures (150, 160, 170 and 180 °C) and feed flow (4.5, 7.5, 10.5 mL/min). The obtained powders were characterized by determining the proximate composition, antioxidant activity, microstructure, fatty acids' profile, and starch and proteins' structures. A correlation among the drying parameters and the chemical and functional attributes of the powders was addressed using principal component analysis. From a technological viewpoint the use of moderate feed flows (7.5 mL/min) and high inlet temperatures (180 °C) was the best combination to obtain high powder yields (85% d.b.), low aw (0.047 ± 0.005) and high solids content (0.956 ± 0.005). The drying temperature positively affected the structure of starch, improving swelling and favoring moderate agglomeration which increases the encapsulation properties of quinoa. These results support the use of spray-drying as a suitable method to obtain powdered extracts of quinoa without affecting the nutritional value, thus supporting their use as functional ingredients in the formulation of ready-to-eat foods.